The Demand for Economic Narratives - Sebastian Blesse; Klaus Gründler; Philipp Heil; Henning Hermes (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Economic narratives are pervasive in the public discourse and can shape individual behavior. But so far we know very little about whether households actually demand and value narratives as information. We combine a comprehensive expert survey with a large-scale nationally representative household sample in the U.S. to examine the demand for economic narratives in a high-stakes environment of an unprecedentedly high recession probability. We document a substantial willingness to pay for economic narratives of more than 4 USD, which is higher than for numerical forecast information. The dominant motives for acquiring narratives are intrinsic, but a smaller share of participants also lists instrumental motives. Economic narratives improve respondents' understanding of recession drivers and shape beliefs about the economy and spending, but exert only a minor impact on quantitative expectations. Our findings underscore the potential of narratives as a tool to improve economic understanding and to foster more informed decision-making.
Keywords: D83; D84; D12; E32; E71; 330; narratives; experts; information acquisition; willingness to pay; expectation formation; belief formation; spending ontentions; recession